Formation of soliton complexes in dispersive systems - Bogdan, M.M.; Kosevich, A.M.; Maugin, G.A. (Condensed Matter Physics, 1999)
The concept of soliton complex in a nonlinear dispersive medium is formulated. It is shown that interacting identical topological solitons in the
medium can form bound soliton complexes which move without radiation.
This phenomenon is considered to be universal and applicable to various physical systems. The soliton complex and its “excited” states are described analytically and numerically as solutions of nonlinear dispersive
equations with the fourth and higher order spatial or mixed derivatives.
The dispersive sine-Gordon, double and triple sine-Gordon, and piecewise
models are studied in detail. Mechanisms and conditions of the formation
of soliton complexes, and peculiarities of their stationary dynamics are investigated. A phenomenological approach to the description of the complexes and the classiﬁcation of all the possible complex states are proposed. Some examples of physical systems, where the phenomenon can
be experimentally observed, are brieﬂy discussed. Формулюється концепція солітонних комплексів в нелінійному дисперсійному середовищі. Показано, що взаємодіючі тотожні топологічні солітони у такому середовищі здатні утворювати солітонні комплекси, що рухаються без випромінювання. Вважається, що це явище є універсальним і зустрічається у різних фізичних системах. Солітонні комплекси і їхні збуджені стани описуються аналітично і чисельно як розв’язки нелінійних дисперсійних рівнянь з четвертою і
вищими просторовимі і змішаними похідними. Ретельно вивчаються дисперсійні системи синус-Гордон, подвійний і потрійний синус-Гордон, а також кусково-лінійна модель. Досліджуються механізми і
умови формування солітонних комплексів і особливості їхньої стаціонарної динаміки. Запропоновано феноменологічний підхід до описання комплексів і класифікацію усіх можливих їхніх станів. Стисло
розглянуті кілька прикладів фізичних систем, в яких це явище може
експериментально спостерігатись.